Analysis of Reservoir Water Storage and Management in the SIER Industrial Zone - Muchamad Idam Choliq; Esti Wulandari; Laksono Djoko Nugroho (International Journal of Industrial Innovation and Mechanical Engineering, 2025)
This study analyzes the water storage capacity and operational patterns of reservoirs in the Surabaya Industrial Estate Rungkut (SIER) to support efficient and sustainable water resource management. The research adopts a quantitative approach by collecting hydrological data, analyzing storage capacity, and simulating reservoir operations based on seasonal scenarios. The findings indicate that SIER's reservoirs have sufficient capacity to meet industrial water demands, although a supply deficit occurs for four months annually. Technical optimization efforts, such as sediment dredging, have proven to increase storage capacity by more than 200%. Practical recommendations for reservoir management include sedimentation normalization and planned operational strategies. These findings are expected to serve as a reference for other industrial zones in addressing water management challenges due to climate variability and increasing industrial demands.